Mesenchymal-Epithelial Transition Exon 14 Skipping Mutation and Amplification in 5,008 Patients With Lung Cancer - Song, Yaolin; Li, Guangqi; Ju, Kun; Ran, Wenwen; Zhao, Han; Liu, Xianglan; Hou, Mingyu; He, Yulu; Chen, Yang; Zang, Guoliang; Xing, Xiaoming (Frontiers in Oncology, 2021)
Background: Lung cancer is a major health concern worldwide because of its increasing incidence and mortality. This study aimed to clarify the association between mesenchymal-epithelial transition (MET) genomic alterations and clinical characteristics of lung cancer. Method: We collected data from 5008 patients with lung cancer diagnosed and treated between January 2017 and July 2021 at the Affiliated Hospital of Qingdao University. Genomic alterations in the MET gene, including the exon 14 skipping mutation and amplification, were detected using amplification refractory mutation system-polymerase chain reaction (2057 cases) and next-generation sequencing (2951 cases). Clinical characteristics such as age, sex, tumor location, tumor stage, smoking, pleural invasion, and histology were statistically analyzed for MET exon 14 skipping mutation and amplification. The DNA splicing sites causing the MET exon 14 skipping mutation at the mRNA level were also investigated. Results: The incidence of the MET exon 14 skipping mutation was 0.90% (41/4564) in adenocarcinoma, 1.02% (3/294) in squamous cell carcinoma, and 8.33% (1/12) in sarcomatoid carcinoma specimens. It was more frequently observed in patients over 60 years of age than the MET exon 14 skipping mutation wildtype. The MET exon 14 skipping mutation co-occurred with epidermal growth factor receptor (EGFR) L858R, EGFR 19-Del, and BRAF V600E mutations. At the DNA level, single nucleotide mutation and small fragment deletion (1–38 base pairs) upstream and downstream of MET exon 14 led to MET exon 14 skipping mutation at the mRNA level. MET amplification occurred in 0.78% (21/2676) adenocarcinoma and 1.07% (2/187) squamous cell carcinoma specimens and was significantly associated with advanced tumor stages (III + IV) compared to the MET amplification wildtype. MET amplification primarily co-occurred with the EGFR mutation. Conclusions: Our study found that MET genomic alterations were statistically related to age and tumor stage and co-existed with mutations of other oncogenic driver genes, such as EGFR and BRAF. Moreover, various splicing site changes at the DNA level led to the exon 14 skipping mutation at the mRNA level. Further studies are required to clarify the association between MET genomic alterations and prognosis.